Synthesis and evaluation of novel dental monomer with branched carboxyl acid group. Issue 7 (5th March 2014) - Song, Linyong; Ye, Qiang; Ge, Xueping; Misra, Anil; Laurence, Jennifer S.; Berrie, Cynthia L.; Spencer, Paulette
Abstract To enhance the water miscibility and increase the mechanical properties of dentin adhesives, a new glycerol‐based monomer with vinyl and carboxylic acid, 4‐((1, 3‐bis(methacryloyloxy)propan‐2‐yl)oxy)‐2‐methylene‐4‐oxobutanoic acid (BMPMOB), was synthesized and characterized. Dentin adhesive formulations containing 2‐hydroxyethyl methacrylate (HEMA), 2, 2‐bis[4‐(2‐hydroxy‐3‐methacryloxypropoxy) phenyl]propane (BisGMA), and BMPMOB were characterized with regard to real‐time photopolymerization behavior, water sorption, dynamic mechanical analysis, and microscale three‐dimensional internal morphologies and compared with HEMA/BisGMA controls. The experimental adhesive copolymers showed higher glass transition temperature and rubbery moduli, as well as improved water miscibility compared to the controls. The enhanced properties of the adhesive copolymers indicated that BMPMOB is a promising comonomer for dental restorative materials. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1473–1484, 2014.